Marking Techniques for Targeted Axillary Dissection Among Patients With Node-Positive Breast Cancer Treated With Neoadjuvant Chemotherapy - Gante, Inês (2023)
Invasive breast cancer with axillary lymph node (LN) invasion is a continuing problem worldwide. The morbidity associated with axillary LN dissection along with the high rate of nodal downstaging after neoadjuvant chemotherapy (NACT) made the standard treatment shift towards less invasive surgery. Sentinel lymph node biopsy (SLNB) after NACT is associated with high false-negative rates (13%-14%). To overcome this problem, it was concluded that the positive nodes should first be indicated with image-detectable markers and then removed together with SLNB: targeted axillary dissection (TAD). This review aims to describe and evaluate the different marking techniques for TAD in patients with node-positive breast cancer treated with NACT, namely: clip placement and guidewire localization; clip placement and 125I-labelled radioactive seed localization; clip placement and skin mark; clip placement and intraoperative ultrasound; tattooing with a sterile black carbon suspension; magnetic seeds; radar and infrared light technology localization. Targeted axillary dissection techniques have shown false-negative rates below 9% and identification rates above 95%. The most studied technique is guidewire localization, as it is also the oldest one. However, according to data gathered from this review, some newer techniques have shown to be very promising due to their statistical results and management factors.